Business Method Patents in Europe and their Strategic Use - Evidence from Franking Device Manufacturers - Stefan Wagner (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2006)
There has been a wide-spread misconception based on the imprecise wording of Art. 52 of the European Patent Convention (EPC) that the protection of business methods by patents is prohibited in Europe. This paper investigates the legal framework set by patent laws with respect to the patentability of business methods, contrasting the situation in lege in Europe and the situation in the US. It is shown that in praxi business methods have never been excluded from patentability in Europe. In the empirical part of the paper, 1,901 European patent applications relating to business methods are identified and major patent indicators are computed. Further, a case study from the franking device industry which is characterized by strong competition for intellectual property rights is conducted. It contains evidence for the strategic use of business method patents leading to opposition rates against granted patents of 44%.
urn:nbn:de:bvb:19-epub-1265-7
Keywords: L39; O34; 650; business method patents; European Patent Office